(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The text explores the discussions about the curricular proposal of the 2015 BNCC that led to a break with the Eurocentric paradigm in the teaching of history content by proposing an Atlantic approach. It is proposed to reflect on the way in which the idea of Atlantic history, although outlined, was operationalized in the first attack of curricular organization from this perspective and provoked an effective break with the Eurocentric paradigm, so rooted in curricular organization in the Brazilian educational system. The analysis was performed by consulting the official document and texts produced by faculty associations, research groups and scholars because of the controversial public / academic debate established and specialized literature.